Pathways to Adolescent Self-Esteem: The Mediating Role of Self-Compassion Between Self-Acceptance and Peer Support - Mujadid Nazifah Gesti Ali; Rezki Hariko (Grief and Trauma, 2026)
Adolescent self-esteem is a critical psychological construct that shapes mental health and academic functioning. This study examines the structural model of relationships among self-acceptance, self-compassion, peer support, and self-esteem in adolescents, with a specific focus on testing the mediating role of self-compassion. Using a quantitative explanatory design, data were collected from 329 adolescents in South Solok Regency, West Sumatra, through cluster random sampling. Instruments included the Coopersmith Self-Esteem Inventory (CSEI), Bloom Self-Acceptance Scale (BSAS) , Self-Compassion Scale (SWD), and Peer Support Perception Scale (PSPS) . Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 to test the structural model and its mediating effects. Results of the structural model testing indicated that peer support and self-compassion significantly and directly predicted self-esteem, while self-acceptance did not show a significant direct effect. However, self-compassion fully mediated the relationship between self-acceptance and self-esteem, and partially mediated the relationship between peer support and self-esteem. Collectively, the three variables explained 59.0% of the variance in self-esteem (R² = 0.590). These findings highlight self-compassion as a pivotal psychological mechanism through which both internal and external factors shape adolescent self-esteem. Implications for school counseling services are discussed, particularly the need to integrate self-compassion development and peer support enhancement into guidance and counseling programs.